2014
DOI: 10.1530/joe-13-0417
|View full text |Cite
|
Sign up to set email alerts
|

Hypooxytocinaemia in obese Zucker rats relates to oxytocin degradation in liver and adipose tissue

Abstract: The metabolic action of oxytocin has recently been intensively studied to assess the ability of the peptide to regulate energy homeostasis. Despite the obvious weight-reducing effect of oxytocin observed in experimental studies, plasma oxytocin levels were found to be unchanged or even elevated in human obesity. The aim of our study was to evaluate the changes in the oxytocin system in Zucker rats, an animal model closely mirroring morbid obesity in humans. Plasma oxytocin levels were measured in obese Zucker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
5
53
0
1
Order By: Relevance
“…Body composition was measured at the end of the washout study. Oxytocin continued to reduce weight gain in this subset of animals between infusion days [29][30][31][32][33][34][35][36][37][38][39] (Fig. 6E).…”
Section: Study 8: Effects Of Treatment Cessation On Food Intake Bodymentioning
confidence: 81%
See 2 more Smart Citations
“…Body composition was measured at the end of the washout study. Oxytocin continued to reduce weight gain in this subset of animals between infusion days [29][30][31][32][33][34][35][36][37][38][39] (Fig. 6E).…”
Section: Study 8: Effects Of Treatment Cessation On Food Intake Bodymentioning
confidence: 81%
“…In addition, chronic central or systemic oxytocin increases epididymal white adipose tissue expression of hormone sensitive lipase (a key mediator of adipocyte lipolysis) (1, 23) while reducing expression of fatty acid synthase (an enzyme linked to lipogenesis) in rats (1). While it remains to be determined whether chronic CNS infusions of oxytocin increase circulating levels (23) in sufficient concentrations to trigger a peripheral effect on lipolysis, it is possible that these effects in our model may be attributed, in part, to a direct effect on adipocytes (60,83,94) where OTRs are expressed (1,31,32,60,83,94,101) or an indirect mechanism. The mechanism underlying these effects may involve outgoing polysynaptic sympathetic nervous system projections from PVN oxytocin neurons to both inguinal (86) and epididymal white adipose tissue (86,89).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the cause of decreased BW induced by oxytocin treatment depends not only on the decreased food intake, but also on the stimulation of lipolysis. Oxytocin receptors are expressed in various tissues, including adipose tissue [38,92], and previous articles reported that oxytocin increases lipolysis and fatty acid β-oxidation by acting directly on adipose tissue in rats [29,136]. Blevins et al [34] demonstrated that, in addition to rodents, subcutaneous oxytocin treatment reduces BW in diet-induced obesity primates (rhesus monkey) with decreased food intake, increased energy expenditure, and lipolysis.…”
Section: Clinical Implications Of Oxytocinmentioning
confidence: 99%
“…Nasal treatment of oxytocin was also reported to decrease food intake in both mice and humans [24,35,36]. However, this reduction of BW is not only induced by food intake reduction; oxytocin also induces lipolysis in adipose tissue and decreases fat mass [29,34,[37][38][39][40]. Recent studies have clarified the various new mechanisms of oxytocin's anorexigenic effects through the CNS and promotion of catabolic reactions on peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%